2000
DOI: 10.1093/ptj/80.10.974
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Model of Gross Motor Function for Children With Cerebral Palsy

Abstract: Background and Purpose. Development of gross motor function in children with cerebral palsy (CP) has not been documented. The purposes of this study were to examine a model of gross motor function in children with CP and to apply the model to construct gross motor function curves for each of the 5 levels of the Gross Motor Function Classification System (GMFCS). Subjects. A stratified sample of 586 children with CP, 1 to 12 years of age, who reside in Ontario, Canada, and are known to rehabilitation centers pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
418
1
38

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 809 publications
(461 citation statements)
references
References 23 publications
4
418
1
38
Order By: Relevance
“…18 The Gross Motor Function Classification System (GMFCS) is used to record the severity of gross motor function impairments on a five-level scale, with children at levels I and II being able to walk without support, while children at level V are unable to walk. 19 Study participants' GMFCS level was reported by parents, and confirmed by reference to data recorded in the Cerebral Palsy Register of Norway. In accordance with the study by Gurka et al, 8 we divided the participants into two groups: GMFCS I and II, defined as children with less severe motor impairments, and GMFCS III to V, defined as children with more severe motor impairments.…”
Section: Other Variables (And Covariates)mentioning
confidence: 87%
“…18 The Gross Motor Function Classification System (GMFCS) is used to record the severity of gross motor function impairments on a five-level scale, with children at levels I and II being able to walk without support, while children at level V are unable to walk. 19 Study participants' GMFCS level was reported by parents, and confirmed by reference to data recorded in the Cerebral Palsy Register of Norway. In accordance with the study by Gurka et al, 8 we divided the participants into two groups: GMFCS I and II, defined as children with less severe motor impairments, and GMFCS III to V, defined as children with more severe motor impairments.…”
Section: Other Variables (And Covariates)mentioning
confidence: 87%
“…Studies have proved GMFM to be reliable and valid. [5][6][7] Provided an alpha level of 5%, a beta of 20%, and a minimal relevant difference of 10%, the sample size was calculated at seven participants per group based on the known variability of the test. 2 Three children, two from the I group, one from the C group, dropped out after randomization but before intervention started; one due to family circumstances, one because the parents had second thoughts about their child's participation in the I group, and one because the parents wanted to try alternative treatment.…”
Section: Intervention and Analysismentioning
confidence: 96%
“…Nominal group and Delphi survey consensus methods were used with independent classification of 77 children by 51 therapists. 4 Using 'concurrent validity' it was possible to demonstrate that GMFM scores generally varied significantly by GMFCS level 9,10 and that the overall correlation between the measure and the classification was very high at -0.91. 9 Stability of classification levels over time has been explored using chart reviews of prospectively collected data 11 and by analyzing data on 656 children with CP classified a mean of 4.3 times at 6 or 12 month intervals.…”
Section: Development Processmentioning
confidence: 99%